2019
DOI: 10.1111/ajad.12921
|View full text |Cite
|
Sign up to set email alerts
|

Review: Sex‐Based Differences in Treatment Outcomes for Persons With Opioid Use Disorder

Abstract: Background and Objectives: In order to address the current opioid crisis, research on treatment outcomes for persons with OUD should account for biological factors that could influence individual treatment response. Women and men might have clinically meaningful differences in their experience in OUD treatment and might also have unique challenges in achieving successful, long-term recovery. This review summarizes and synthesizes the current literature on sex-based differences in OUD treatment outcomes. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 61 publications
4
69
0
Order By: Relevance
“…We predicted that buprenorphine would effectively decrease fentanyl-seeking in both sexes given findings in humans showing that it improves treatment retention and reduces opioid use in both women and men with an OUD (Herget 2005 ; Mattick et al 2014 ). However, because the clinical findings have been mixed regarding the potential for buprenorphine to have differential efficacy as an anti-relapse intervention in men versus women (Koons et al 2018 ; Huhn et al 2019 ), we did not have a prior prediction for sex differences in the efficacy of buprenorphine to reduce fentanyl-seeking. While our findings showing that buprenorphine markedly reduced fentanyl-seeking in both sexes support this hypothesis, we also have some evidence to suggest that its efficacy may be enhanced in females versus males given that buprenorphine was able to eliminate sex differences in drug-seeking, bringing females down to a male level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We predicted that buprenorphine would effectively decrease fentanyl-seeking in both sexes given findings in humans showing that it improves treatment retention and reduces opioid use in both women and men with an OUD (Herget 2005 ; Mattick et al 2014 ). However, because the clinical findings have been mixed regarding the potential for buprenorphine to have differential efficacy as an anti-relapse intervention in men versus women (Koons et al 2018 ; Huhn et al 2019 ), we did not have a prior prediction for sex differences in the efficacy of buprenorphine to reduce fentanyl-seeking. While our findings showing that buprenorphine markedly reduced fentanyl-seeking in both sexes support this hypothesis, we also have some evidence to suggest that its efficacy may be enhanced in females versus males given that buprenorphine was able to eliminate sex differences in drug-seeking, bringing females down to a male level.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, as the COVID-19 global pandemic continues, there are concerns that the opioid epidemic is worsening with reports from national, state, and local media suggesting an increase in opioid-related mortality in more than 30 states, particularly from illicitly manufactured fentanyl and fentanyl analogs (American Medical Association 2020 ). Effects of the opioid epidemic are widespread, and women are at a particularly high risk (Hemsing et al 2016 ; Koons et al 2018 ; Mazure and Fiellin 2018 ; Huhn et al 2019 ) as they are more likely than men to be prescribed opioids and to misuse prescription opioids (Koons et al 2018 ; Hirschtritt et al 2018 ). Although men have historically had higher rates of OUD than women, differences have narrowed in the current opioid epidemic (i.e., 2.3:1 male-to-female ratio in 2002 versus a 1.8:1 ratio in 2018; National Survey on Drug Use and Health 2020 ) with use increasing at a faster rate in women versus men (i.e., 283% versus 108% increase in heroin use from 2007 to 2014; Marsh et al 2018 ; Mazure and Fiellin 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…20 Not surprisingly, women receiving treatment for an OUD are more likely to have comorbid mental health problems (eg, depression), and there is some evidence that previous traumatic experiences may trigger relapse. 24 It is probable that childhood trauma independently increases the risk of an adverse parenting style and/or suboptimal parentechild attachment. Furthermore, the impact of parental opioid use on child development is likely mediated by the involvement of other nondrug-using adults in the child's life.…”
Section: Impact Of Opioid Use On Parentingmentioning
confidence: 99%
“…A recent systematic review concluded that women have a higher need for cooccurring treatment to address their mental health problems, and although there were few sex differences in treatment outcomes, women treated with buprenorphine may have lower relapse rates compared with male clients. 24 Even when parents can access treatment for OUDs, it may be for an insufficient duration. Previous research has found that >50% of pregnant women who need SUD treatment receive it only during the postpartum period.…”
Section: Role Of Parental Treatmentmentioning
confidence: 99%
“…Many of these populations are susceptible to OUD and have been highlighted as having unique needs for treatment [121,122]. Furthermore, the effectiveness of interventions among those with OUD has also been shown to differ by sex [123]. Within our set of included trials, study populations were predominantly composed of men, with almost a third comprising at least 75% males.…”
Section: Limitationsmentioning
confidence: 99%